Evaluasi Kualitas Sistem Informasi Usulan Formasi Aparatur Sipil Negara Berbasis CodeIgniter Menggunakan E-GovQual - Arsaela Astikasari; Sri Huning Anwariningsih; Hardika Khusnuliawati (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
The submission of proposals for Civil Servant (ASN) positions in Klaten Regency has been done manually so far, resulting in an inefficient data management process across various Regional Government Organizations, prone to input errors, and complicating the data validation, monitoring, and recapitulation processes. This research aims to develop an ASN Formation Needs Proposal Information System, which simplifies the management of employee formation proposals by providing employee data, job requirements, and retirement projections based on Job Analysis and Workload Analysis, and to evaluate its quality. The system development method employs a waterfall approach, comprising the stages of requirements analysis, system design, implementation (coding), system testing, and maintenance. The results of system testing with E-GovQual on the variables (Efficiency, Trust, Reliability, and Citizen Support) indicate that all instrument items are deemed valid and reliable, with Cronbach's Alpha values for each variable exceeding 0.7. From the E-GovQuav testing, it was found that attributes EF3, TRS2, RLB5, and CS2 were identified as the most influential factors on system quality. This research suggests that this system can assist Regional Apparatus Organizations in structuring their proposals for staffing needs and enable the Personnel and Human Resources Development Agency (BKPSDM) to verify, analyze, and recapitulate data on staffing needs proposals more efficiently and accurately. This system can be an optimal solution in supporting transparency and accuracy in managing ASN staffing needs proposals in Klaten Regency